Context specific safe water supply technologies for vulnerable climatic and geomorphologic areas of Bangladesh (BRAC University Journal, 2026)
The detection of arsenic in shallow groundwater threatens groundwater based water supply in Bangladesh. Seawater encroachment in coastal aquifers is another major problem for the availability of fresh water. On the other hand, surface water source is not suitable in many parts of the country. In addition, vu1nerable climatic conditions and anticipated impact of climate change arc putting more stress on the sustainable development of safe water resources. Therefore, one technology is not suitable for all areas due to different hydro meteorological conditions. The aim of this paper is to determine sustainable context-specific water supply technologies considering the climatic hazard and other vu1nerabilities in 5 different hard to reach (HtR) areas, which are (a) drought prone, (b) flood prone, (c) char (sand bar), (d) coastal and (e) haor (swamp) areas. It is found from the study that more activities and effort is needed to ensure the water supply facilities for all, mainly in the HtR areas. Still expansion and improvement of the water supply services is required to satisfy the basic needs in these areas. Proper maintenance and monitoring of existing appropriate technologies arc also important for sustainable use. Guidelines and user manuals need to be prepared as a tool to standardized procedures for installation and easy maintenance of technologies.